THE EXTRA-TERRITORIAL JURISDICTION IN THE CASE-LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS AND CONTEMPORARY CHALLENGES - Popović, Igor (Politeia, 2023)
The paper analyses the concept of extra-territorial jurisdiction as envisaged by the Euroepan Convention on Human Rights (ECHR). This concept of jurisdiction implies an answer to the question whether a person outside the territory of a state can be considered to be under its jurisdiction, and thus whether the ECHR Party can violate any of their proclaimed rights. Initially, the author briefly discusses the concept of extra-territorial jurisdiction in The European Court of Human Rights case law (ECtHR). The author comes to the conclusion that the Court’s jurisprudence is not clear or consistent. As a result, the article examines three alternative approaches to extra-territorial jurisdiction that are clear, reality-based, and human rights friendly. These three approaches involve the test of negative and positive obligations, the functionality test, and the control of rights test. In addition, the author considers three contemporary challenges that the ECtHR may face in the fields of migration, ‘green’ issues, and the use of modern technologies. The author claims that the ECtHR’s understanding of jurisdiction is insufficient for modern challenges. The alternative approaches could be a viable answer to such issues.